Chapter 13. An empirical evaluation of blockchain technology: challenges and opportunities for Islamic cryptoassets - Zaman, Asif (Islamic finance in the digital age, 2024)
Conventional finance considers cryptocurrency (money) as commodity for trade purpose which contradicts with the Islamic perspective of cryptocurrency (money), to treat money as medium of exchange rather commodity. The purpose of this chapter is threefold. First, to critically explore Blockchain technology and the emergence of Islamic cryptoassets. Second, to evaluate the regulatory challenges and opportunities for using Blockchain technology in the development and proliferation of Islamic cryptoassets. Third, to empirically investigate whether Islamic Blockchain technology (Islamic gold backed cryptoassets and Islamic DeFi tokens) provide safe havens (benefits) to equity markets in emerging Muslim countries. For empirical investigation and volatility transmission of Islamic cryptoassets to stock markets of emerging Islamic countries, DCC-GARCH model is employed. Overall, the findings show no evidence of co-movements among cryptoassets and stock market volatilities. Thus, in general, three Islamic cryptoassets studied in this chapter could be considered as safe-haven (beneficial) assets for Islamic stock markets.